Transport of steroid 3-sulfates and steroid 17-sulfates by the sodium-dependent organic anion transporter SOAT (SLC10A6). Issue 179 (May 2018) - Grosser, Gary; Bennien, Josefine; Sánchez-Guijo, Alberto; Bakhaus, Katharina; Döring, Barbara; Hartmann, Michaela; Wudy, Stefan A.; Geyer, Joachim
Highlights: SOAT transports the 3'-monosulfates 17α-OH-PREGS, androsterone sulfate, and epiandrosterone sulfate. SOAT transports the 17'-monosulfates 17β-estradiol-17-sulfate, testosterone sulfate (TS), epi-TS, and 5α-dihydro-TS. The 3'- and 17'-monosulfate groups of the SOAT substrates have flexibility for α- or β-orientation. SOAT has no transport activity for 17β-estradiol-3, 17-disulfate, although this steroid is an inhibitor of SOAT. Abstract: The sodium-dependent organic anion transporter SOAT/Soat shows highly specific transport activity for sulfated steroids. SOAT substrates identified so far include dehydroepiandrosterone sulfate, 16α-hydroxydehydroepiandrosterone sulfate, estrone-3-sulfate, pregnenolone sulfate, 17β-estradiol-3-sulfate, and androstenediol sulfate. Apart from these compounds, many other sulfated steroids occur in mammals. Therefore, we aimed to expand the substrate spectrum of SOAT and analyzed the SOAT-mediated transport of eight different sulfated steroids by combining in vitro transport experiments in SOAT-transfected HEK293 cells with LC–MS/MS analytics of cell lysates. In addition, we aimed to better understand the structural requirements for SOAT substrates and so selected structural pairs varying only at specific positions: 3α/3β-sulfate, 17α/17β-sulfate, mono-sulfate/di-sulfate, and 17α-hydroxylation. We found significant and sodium-dependent SOAT-mediated transport of 17α-hydroxypregnenolone sulfate, 17β-estradiol-17-sulfate, androsterone sulfate, epiandrosterone sulfate, testosterone sulfate, epitestosterone sulfate, and 5α-dihydrotestosterone sulfate. However, 17β-estradiol-3, 17-disulfate was not transported by SOAT. In conclusion: SOAT substrates from the group of sulfated steroids are characterized by a planar and lipophilic steroid backbone in trans-trans - trans conformation of the rings and a negatively charged mono-sulfate group at positions 3′ or 17′ with flexibility for α- or β- orientation. Furthermore, 5α-reduction, 16α-hydroxylation, and 17α-hydroxylation are acceptable for SOAT substrate recognition, whereas addition of a second negatively charged sulfate group seems to abolish substrate binding to SOAT, and so 17β-estradiol-3, 17-disulfate is not transported by SOAT.